Rancang Bangun Sistem Informasi Pengajuan Cuti Di Direktorat KPLP Dengan Metode Extreme Programming - Faris Akbar; Savitri (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
This study aims to develop a web-based employee leave application information system design at the Directorate of Sea and Coast Guard Unit (KPLP) using PHP programming language and laravel framework as a framework, as well as adaptive and communicative Extreme Programming methods. Manual leave management causes several obstacles, such as employees not knowing the amount of leave remaining and applying for leave still using paper forms that require various stages until the leave report is validated. This research uses a qualitative approach with case study methods and data collection through observation, interviews, and documentation. The data was then analyzed using triangulation techniques. In this case, a web-based employee leave application information system developed using PHP programming language and laravel framework as the framework, as well as the Extreme Programming method as the method, can be the right solution to overcome problems in managing employee leave that is still manual. With the developed information system, employees can easily find out the amount of leave remaining and apply for leave online, improve the effectiveness and efficiency of employee leave applications, and the security of leave data. This research is expected to provide benefits for companies and academics.